2019
DOI: 10.1007/s10592-019-01145-9
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distances and ocean currents influence Caribbean Acropora palmata population connectivity in the Lesser Antilles

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 91 publications
3
7
0
Order By: Relevance
“…IBD is driven by distance-limited dispersal (Wright 1943 ; Aguillon et al 2017 ), which is consistent with the short planktonic duration common for lecithotrophic sponge larvae. IBD patterns were also observed in the coral A. palmata in this area (Japaud et al 2019 ), and have been found in other sponges at similar spatial scales elsewhere (Bell et al 2014 ; Pérez-Portela et al 2015 ; Riesgo et al 2016 ). However, many sponge studies have found IBD to be absent or very weak, with oceanographic conditions forming better predictors of population structure (Giles et al 2015 ; Taboada et al 2018 ; Riesgo et al 2019 ).…”
Section: Discussionsupporting
confidence: 75%
“…IBD is driven by distance-limited dispersal (Wright 1943 ; Aguillon et al 2017 ), which is consistent with the short planktonic duration common for lecithotrophic sponge larvae. IBD patterns were also observed in the coral A. palmata in this area (Japaud et al 2019 ), and have been found in other sponges at similar spatial scales elsewhere (Bell et al 2014 ; Pérez-Portela et al 2015 ; Riesgo et al 2016 ). However, many sponge studies have found IBD to be absent or very weak, with oceanographic conditions forming better predictors of population structure (Giles et al 2015 ; Taboada et al 2018 ; Riesgo et al 2019 ).…”
Section: Discussionsupporting
confidence: 75%
“…S5) in contrast to earlier findings that backcrosses are restricted to introgression of A. palmata genes into the A. cervicornis genome. A recent report also found putative A. palmata backcrosses based on microsatellite data in the Lesser Antilles 62 . Together, these results support the conclusion of bidirectional introgression in Caribbean acroporids.…”
Section: A Muricatamentioning
confidence: 83%
“…Besides the impact of latitude and host biology, geographic factors also likely contribute to the evolutionary dynamics of the CsRV1. Studies revealed the restricted population connectivity and short-distance dispersal of coral ( Acropora palmata ) and sponge ( Ircinia campana ) larvae in the Caribbean, limited by geographic distances among habitats [ 93 , 94 ]. Similarly, blue crab habitats in the CAR areas are also likely to be isolated islands linked by larval transport, with fewer opportunities for juvenile or adult migration between islands.…”
Section: Discussionmentioning
confidence: 99%